The importance of humanities in the construction of knowledge: perspectives in Giambattista Vico - Silva, João Alberto Mendonça; Reis, Álisson Muryel dos; Maciel, Josemar de Campos (Universidade Estadual de Campinas, 2019)
The present article will address the construction of knowledge in Giambattista Vico based on the discourse of Nostri Temporis Studiorum. With the exchange of "imagination" for "rationality," human ingenuity was put aside, thus nullifying the verisimilitude which had been denied by not presenting factual truths leading to the atrophy of ingenuity. The purpose here is to analyze the imaginative development proposed by Vico, generating a new criticism. It concludes on a possible epistemology of the humanities, in which each subject can, with his own instruments, develop a less "dogmatic" and more human knowledge, starting from a stable soil, that is, history.